Caspar Bauhin (1560-1624): Swiss anatomist and reformer of anatomical nomenclature - Ghosh, Sanjib Kumar (Italian Journal of Anatomy and Embryology, 2016)
Caspar Bauhin (1560-1624) was a Swiss anatomist, physician and botanist. He commenced the study of medicine at a young age in Basel but had to move to Padua after an outbreak of plague in his native place. In Padua, he was privileged to study under Fabricius ab Aquapendente, an accomplished anatomist of his time, and other pioneers in the field of medicine, surgery and botany. He travelled extensively through Italy, France and Germany before finally returning to Basel, where he started to conduct public anatomy dissections and in due course was appointed to the Chair of Anatomy and Botany at the University of Basel. His treatise, Theatrum anatomicum (1605), was considered as the finest comprehensive text in anatomy during that period. Theatrum was highly appreciated as it followed a systemic approach with focus on anatomical anomalies and had a useful set of illustrations. His major contribution to Anatomy was the introduction of a descriptive terminology which replaced the prevalent trend of naming the structures with ordinal numbers and cleared the confusion among anatomists in relation to identification of structures. He was the first to describe the anterior lingual glands (Bauhin’s gland), which are seromucous glands located near the tip of tongue. He is presumed to be the first to report the ileocecal valve, which is also known as Bauhin’s valve. Bauhin’s contributions are a true testimony of his legacy in the domain of anatomical sciences.